Total phenolic content and antioxidant activity of ginger extract and SNEDDS with eel fish bone oil (Anguilla spp.) - IMAS IFRIAN WIJAYANTI; AGUNG BUDIHARJO; ARTINI PANGASTUTI; FEA PRIHAPSARA; ANIF NUR ARTANTI (Nusantara Bioscience, 2018)
Wijayanti II, Budiharjo A, Pangastuti A, Prihapsara F, Artanti AN. 2018. Total phenolic content and antioxidant activity of ginger extract and SNEDDS with eel fish bone oil (Anguilla spp.). Nusantara Bioscience 10: 164-169. Aims of this study were to measure phenolic content of ginger (Zingiber officinale) and to observe the comparison of antioxidant activity between pure ginger extract and ginger extract in SNEDDS (Self Nanoemulsifying Drug Delivery System) with bone of eel fish oil (Anguilla spp.) as a conductor. Analysis was done based on IC50 value using DPPH (2,2 diphenyl-1-picrylhydrazyl) method and activity of Superoxide Dismutase (SOD) in vivo using Adrenochrome Assay. Determination of total phenolic content of ginger extract was measured by UV/Vis Spectrophotometric using Folin-Ciocalteau reagents then the absorbances were measured at wavelength 756 nm. Calculation of IC50 DPPH of the ginger extract and SNEDDS were measured using spectrophotometer UV/Vis at 517 nm wavelength. Measurements of SOD was based on the ability of SOD inhibit spontaneous auto reduction of epinephrine using Adrenochrome Assay at 12 male Wistar rats that divided into 4 treatment groups with 3 replicates for each group. Total phenolic content of ginger extract from 3 replications were 4,8519 ± 0,037 µg/mL equivalent with gallic acid standard solutions (GAE) or 485,1847 ± 3,7045 mgGAE/100 g dry weight. Antioxidant scavenging activity by DPPH assay of ginger was higher than SNEDDS. IC50 of ginger was 385.4 mg/mL, and IC50 of SNEDDS was 428.4 mg/mL. The result of descriptive analysis of Kruskal Wallis of SOD activity assay indicated significant differences between treatment groups (P = 0.001 (P <0.05)). SOD activity test performed in vivo showed that ginger extract made into SNEDDS system with eel fish oil used as the conductor has a significant influence compared with ginger extract group.